Lung cancer surgical treatment after solid organ transplantation: A single center 30-year experience. (January 2020) - Drevet, Gabrielle; Duruisseaux, Michaël; Maury, Jean-Michel; Riche, Benjamin; Grima, Renaud; Ginoux, Marylise; Mornex, Jean-François; Tronc, François
Highlights: There is a 6 % mean incidence of cancer in recipients of solid organ transplantation. Risk of lung cancer is estimated from 0.3 % to 0.85 % in the transplant population. Surgical treatment for lung cancer has to be recommended to these patients. Long term survival rate is satisfactory and similar to that of the general population. In transplant recipients with former smoking history, close follow-up is mandatory. Abstract: Objectives: Solid organ transplantation is an accepted treatment for end-stage organ failure. Long-lasting immunosuppressive therapy may increase the risk of de novo malignancies in transplant recipients. Increased risk of bronchogenic carcinoma in this population is controversial but prolonged transplant recipients' survival (obtained in modern transplantation era) may increase the need for lung cancer surgical resection in immunosuppressed patients. Our aim was to assess morbidity, mortality and long-term survival after lung cancer surgical treatment in this population. Materials and methods: In an observational study, the medical charts of all consecutive patients who had undergone surgical treatment for lung cancer after solid organ transplantation were reviewed. These medical records were extracted from the University of Lyon (France) Transplantation database and Thoracic Surgery database. From 1986–2016, 61 patients underwent a surgical treatment for lung cancer after solid organ transplantation. Results: The surgical procedures consisted of 52 lobectomies, 7 pneumonectomies and 2 wedge-resections. 90-day post-operative complications, most of which were pneumonias, affected 31 patients (50.8 %). 90-day postoperative mortality was 9.8 %. Overall survival was 40.6 % at 5 years and 18 % at 10 years. Conclusion: Despite a higher rate of infectious complications and 90-day postoperative mortality, surgical treatment for lung cancer must be offered to these patients as it offers a chance to cure earlier- stage disease. Long-term survival rate is satisfactory and similar to that of the general population. In transplant recipients with former smoking history, close follow-up is mandatory to increase early lung cancer diagnosis.